2005
DOI: 10.1158/1078-0432.ccr-05-0452
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Octasaccharides Inhibit Angiogenesis In vivo

Abstract: Background: In previous experiments, we showed that heparin oligosaccharides inhibit the angiogenic cytokine fibroblast growth factor-2. Here, we present the first in vivo study of sizefractionated heparin oligosaccharides in four models of angiogenesis that are progressively less dependent on fibroblast growth factor-2. Experimental Design: Heparin oligosaccharides were prepared using size-exclusion gel filtration chromatography and characterized through depolymerization and strong anion exchange high-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 29 publications
(36 reference statements)
3
53
0
Order By: Relevance
“…5B). These results confirm previous reports that heparin can inhibit angiogenesis in vivo (36,37). Quantitative real-time PCR analysis of tumor tissues revealed that heparin treatment significantly reduced levels of miR-10b expression when compared with tumors from control animals (Fig.…”
Section: Heparin Impairs Angiogenesis and Attenuates The Growth Of Xesupporting
confidence: 91%
“…5B). These results confirm previous reports that heparin can inhibit angiogenesis in vivo (36,37). Quantitative real-time PCR analysis of tumor tissues revealed that heparin treatment significantly reduced levels of miR-10b expression when compared with tumors from control animals (Fig.…”
Section: Heparin Impairs Angiogenesis and Attenuates The Growth Of Xesupporting
confidence: 91%
“…It is therefore most probable that dp12 is affecting factors other than CXCL12 in mediating its effects on tumour growth. For example, heparin derivatives as short as eight monosaccharide units can bind both FGF-2 and VEGF in vivo Tyrrell et al, 1993;Hurwitz et al, 2004); this prevents these growth factors from binding to heparan sulphate leading to inhibition of angiogenesis (Hasan et al, 2005). As these oligosaccharides prevent FGF-2 and VEGF from binding to heparan sulphate, they function as antagonists of angiogenesis and have been shown in vivo to inhibit the development of new vasculature (Hasan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among the glycosaminoglycan-based pharmaceutics already in clinical use, modulation of angiogenesis by different heparins has been shown. For example, the low molecular weight heparin tinzaparin was found to be a potent angiogenesis inhibitor in vitro (106) and heparin octasaccharides inhibited tumor angiogenesis in animal models (107). Mechanistically, this antiangiogenic effect is due to heparin-induced cellular release of tissue factor pathway inhibitor.…”
Section: Glycosaminoglycans and Proteoglycans As Angiogenesis Inhibitorsmentioning
confidence: 99%